Increased Risk of Cancer and Mortality in a Large French Population-Based Paediatric-Onset Inflammatory Bowel Disease Retrospective Cohort. (1st November 2022) - Dupont-Lucas, Claire; Leroyer, Ariane; Ley, Delphine; Spyckerelle, Claire; Bertrand, Valérie; Turck, Dominique; Savoye, Guillaume; Maunoury, Vincent; Guillon, Nathalie; Fumery, Mathurin; Sarter, Hélène; Gower-Rousseau, Corinne; et al.
Abstract: Background and Aims: Paediatric-onset IBD [pIBD] is associated with an increased risk of cancer and mortality in adulthood. The aims of this study were to measure the incidence of cancer and mortality in patients with pIBD and identify factors associated with mortality and cancer. Methods: All patients diagnosed with Crohn's disease [CD] or ulcerative colitis [UC] before the age of 17 years between 1988 and 2011 in the EPIMAD registry were retrospectively followed until 2013 for cancer and 2015 for mortality. Standardized incidence [SIR] and mortality ratios [SMR] were estimated compared to the general population. Cox regression was used to compare the effect of exposures on cancer and mortality among IBD patients. Results: We included 1344 patients [52% males, 75% CD], totalling 12 957 patient-years for cancer incidence and 18 817 patient-years for mortality. There were 14 cases of cancer [median age 27.8 years] and 15 deaths [median age 28.8 years]. The incidence of cancer and of mortality were increased compared to the general population: all-cancer SIR = 2.7 (95% confidence interval [CI]: 1.5–4.8), SMR = 1.7 [95% CI: 1.0–2.8]. Colorectal cancer had the highest SIR and SMR: SIR = 41.2 [95% CI: 17.2–99.0], SMR = 70.4 [95% CI 22.7–218.2]. Cancer was associated with (hazard ratio [HR], 95% CI): active smoking at diagnosis [5.5, 1.8–16.5], p = 0.002; any exposure to anti-tumour necrosis factor [6.1, 1.7–22.3], p = 0.0065; and exposure to combination therapy [7.4, 1.8–29.7], p = 0.0047. Mortality was associated with extraintestinal manifestations (HR 4.9 [95% CI: 1.7–13.8], p = 0.003). Conclusions: In this large population-based cohort, patients with pIBD had an increased risk of both cancer [2.7-fold] and mortality [1.7-fold], particularly for colorectal cancer. Graphical Abstract: